A Review on A review on significance and failure causes of small-scale irrigation dams in arid and semi-arid lands - Etienne Umukiza; Koffi Felix Abagale; Thomas Apusiga Adongo (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2023)
Water scarcity is increasingly becoming a significant challenge in arid and semi-arid lands. In these areas, small dams and reservoirs are important in providing water resources, supporting agricultural activities, and contributing to sustainable and resilient rural communities as they require an affordable investment. However, their frequent failures pose significant challenges to sustainable water management and agricultural development in these regions. This review study was developed based on the review of many international standards and guidelines from published studies in scientific journals in addition to information from practitioners. We examined the significance and causes of the failure of small dams and reservoirs; and discussed design criteria and considerations involved in their construction. The outcomes of this study offer valuable insights into the significance of small-scale irrigation dams and shed light on the multifaceted causes of their failure. A holistic approach to address the challenges identified are approach is required. Integrating engineering solutions such as improving design, and regular maintenance, with sustainable land management are crucial for optimising the small dams and ensuring that they adequately serve the needs of the community. The causes of failure were found to be multifaceted encompassing factors such as poor construction and maintenance practices and inadequate design considerations. Finally, this review highlighted the key elements in assessing structural conditions critical to the functionality and sustainability of small dams and reservoirs.